2018
DOI: 10.1016/j.jtcvs.2018.01.083
|View full text |Cite
|
Sign up to set email alerts
|

One-year outcomes with the HeartMate 3 left ventricular assist device

Abstract: The novel LVAD HM3 has already shown excellent Conformité Européenne mark trial results. Within this cohort, 1-year survival after HM3 implantation was 85%. The HM3 showed excellent midterm results with 0% stroke and 0% pump thrombosis rates 1 year after implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…(5,6) However, recent data from HeartMate 3 patients has shown an increased rate of 22%-36%. (3,7) VAD-related complications are thought to be the result of non-physiological shear stress patterns causing activation and damage of blood cells and proteins. (8) Red blood cells (RBCs) can tolerate relatively high shear stress in comparison to other blood cell types with hemolysis occurring due to deformation and fragmentation around 200 Pa-300 Pa. (9,10) Flow conditions within VADs disrupt natural hemodynamics through briefly exerting high shear stresses (10 Pa-800 Pa) on platelets.…”
mentioning
confidence: 99%
“…(5,6) However, recent data from HeartMate 3 patients has shown an increased rate of 22%-36%. (3,7) VAD-related complications are thought to be the result of non-physiological shear stress patterns causing activation and damage of blood cells and proteins. (8) Red blood cells (RBCs) can tolerate relatively high shear stress in comparison to other blood cell types with hemolysis occurring due to deformation and fragmentation around 200 Pa-300 Pa. (9,10) Flow conditions within VADs disrupt natural hemodynamics through briefly exerting high shear stresses (10 Pa-800 Pa) on platelets.…”
mentioning
confidence: 99%
“…207,234,247 For HM3, all publications on follow-up have shown low incidence of pump thrombosis. [216][217][218][219][220][248][249][250][251][252] There is one reported case of outflow graft occlusion. 253…”
Section: Thrombosismentioning
confidence: 99%
“… 3 More recently, an analysis from the multicenter study of maglev technology in patients undergoing mechanical circulatory support therapy with heartmate 3 (MOMENTUM 3) trial comparing centrifugal flow HeartMate III with the axial flow HeartMate II demonstrated excellent two years' outcomes with respect to the disabling stroke or malfunctioning of the device. 4 However, nearly two-thirds of the patients experience major adverse events within the first year after LVAD implantation. 5 Among them, stroke (both ischemic and hemorrhagic) is a significant adverse event associated with higher morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%